2013
DOI: 10.1371/journal.pone.0074037
|View full text |Cite
|
Sign up to set email alerts
|

Educational Intervention Improves Anticoagulation Control in Atrial Fibrillation Patients: The TREAT Randomised Trial

Abstract: BackgroundStroke prevention in atrial fibrillation (AF), most commonly with warfarin, requires maintenance of a narrow therapeutic target (INR 2.0 to 3.0) and is often poorly controlled in practice. Poor patient-understanding surrounding AF and its treatment may contribute to the patient’s willingness to adhere to recommendations.MethodA theory-driven intervention, developed using patient interviews and focus groups, consisting of a one-off group session (1–6 patients) utilising an “expert-patient” focussed DV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
241
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(252 citation statements)
references
References 37 publications
(54 reference statements)
5
241
0
4
Order By: Relevance
“…The TREAT study found that baseline specific necessity beliefs were predictive of INR control at 1 year. Furthermore, they established links between baseline negative beliefs about medication and TTR 43. This finding is supported by our analysis where TTR >75% patients have higher necessity beliefs.…”
Section: Discussionsupporting
confidence: 84%
“…The TREAT study found that baseline specific necessity beliefs were predictive of INR control at 1 year. Furthermore, they established links between baseline negative beliefs about medication and TTR 43. This finding is supported by our analysis where TTR >75% patients have higher necessity beliefs.…”
Section: Discussionsupporting
confidence: 84%
“…Unfortunately, other studies have also shown that simple educational interventions may not be sufficient to modify adherence behavior. [49][50][51] Lastly, we examined adherence to antiplatelet therapy at 12 months, since that is standard recommendation after a DES. However, expert opinion and guidelines, as well as the appropriate length of use of such medications continue to evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Pacjenci często nie mają jednak odpowiedniej wiedzy na temat AF -nawet ci, którzy otrzymali ustne i pi- semne informacje [32,1011,1012], co wskazuje na potrzebę dalszego rozwoju usystematyzowanej edukacji pacjentów. Opracowano kilka narzędzi do informowania pacjentów, koncentrujących się głównie na OAC [1013][1014][1015][1016]. Grupa robocza autorów niniejszych wytycznych opracowała specjalną aplikację dla pacjentów z AF w celu wsparcia ich informowania i edukowania.…”
Section: Zintegrowana Edukacja Pacjentówunclassified